Sustainable circular value chains: From rural waste to feasible urban construction materials solutions. (May 2021) - Schmidt, Wolfram; Commeh, Michael; Olonade, Kolawole; Schiewer, Gesine Lenore; Dodoo-Arhin, David; Dauda, Risikat; Fataei, Shirin; Tawiah, Angela Tetteh; Mohamed, Fatma; Thiedeitz, Mareike; Radebe, Nonkululeko W.; Rogge, Andreas
Abstract: Urban regions in sub-Saharan Africa are growing significantly more rapid than their also growing rural counterparts. However, the employment perspectives in rural areas are decreasing, and thus the urban growth can become a driver for enhanced livelihoods in the rural areas. Since urbanisation in Africa requires high amount of concrete, the conversion of agricultural waste materials to sustainable concrete constituents does not only create new rural and urban income possibilities, it can also help Africa's construction industry to spearhead green concrete technologies, and thus to reduce carbon emission worldwide. From vegetable wastes chemical admixtures can be derived as well as reactive mineral cement substitutes, which help to use concrete more efficiently and reduce the ordinary Portland cement clinker in concrete, respectively. The authors of this paper discuss the potentials and shortcomings of using agricultural waste materials for construction materials and propose a synergistic three-step process chain to obtain polysaccharides, biochar, and a reactive ash. The process requires boiling, hydrolysis and vertical shaft kiln technology, respectively, to obtain maximum useable products with minimum generation of climate gases. Eventually, the process chain is discussed in conjunction with possible rural to urban circular economic potentials in the concrete construction business. Highlights: Circular economic value chains from production of urban construction materials based on rural agricultural waste. Rural development potentials from green urban growth. Cement replacement potentials for African economies by using agricultural waste ashes as SCM. Assessment of supply chains for the use of agricultural waste as cement replacement. Multi-step constituent production flow chart - from organic rheology modifying admixture to pozzolanic cement replacement.